Pension reforms in Kazakhstan using an OLG model - Abdikarim, Uldana (Nazarbayev University School of Sciences and Humanities, 2020)
The aim of this paper was to study the effects of recently introduced pension reform in Kazakhstan on the welfare of the country. The effect of increase in mandatory retirement age for women from 58 to 63 was of primary interest of the paper. In order to achieve this goal, I proposed 4-period OLG model with three main sectors of the economy and a fully-funded pension system.